2019
DOI: 10.1212/wnl.0000000000008077
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac electrical instability in newly diagnosed/chronic epilepsy tracked by Holter and ECG patch

Abstract: ObjectiveWe hypothesized that cardiac electrical instability and abnormal autonomic tone result from cumulative cardiac injury sustained in recurrent seizures. We tested this hypothesis by comparing T-wave alternans (TWA) and heart rate variability (HRV), both established markers of sudden cardiac death (SCD) risk, in patients with chronic as compared to newly diagnosed epilepsy.MethodsIn this prospective, observational cohort study, patients (newly diagnosed epilepsy, n = 6, age 41.8 ± 6.8 years; chronic epil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Furthermore, TWA levels appear to depend on the duration of epilepsy, again supporting the notion of acquired cardiac damage. People with chronic epilepsy displayed higher TWA levels than those with newly diagnosed epilepsy, and TWA levels of adults with newly diagnosed epilepsy did not differ from healthy controls [104]. Importantly, PWE had reduced TWA levels and increased HRV upon vagus nerve stimulation (VNS), suggesting that VNS can considerably reverse or compensate epilepsy‐related cardiac dysfunction [102, 103].…”
Section: Epilepsy‐related Cardiac Complicationsmentioning
confidence: 99%
“…Furthermore, TWA levels appear to depend on the duration of epilepsy, again supporting the notion of acquired cardiac damage. People with chronic epilepsy displayed higher TWA levels than those with newly diagnosed epilepsy, and TWA levels of adults with newly diagnosed epilepsy did not differ from healthy controls [104]. Importantly, PWE had reduced TWA levels and increased HRV upon vagus nerve stimulation (VNS), suggesting that VNS can considerably reverse or compensate epilepsy‐related cardiac dysfunction [102, 103].…”
Section: Epilepsy‐related Cardiac Complicationsmentioning
confidence: 99%
“…Ventricular tachycardias, in turn, are facilitated by abnormalities of cardiac repolarization (e.g. prolonged QT intervals, increased QT dispersion, increased T wave alternans) which are commonly found in people with chronic epilepsy [73,74]. Valid ECG predictors for an increased SUDEP risk, however, were not convincingly reported to date [62,75].…”
Section: Sudep and Sudden Cardiac Death -Two Overlapping Entities?mentioning
confidence: 99%
“…The available clinical evidence suggests that recurring seizures impose an imprint on myocardial structural integrity and electrical function that can be detected by the standard electrocardiogram (EKG) and more recently by multiday EKG patches 41,42 39 .…”
Section: A Syndromic Approach To Establishing Clinical Criteria For Epileptic Heartmentioning
confidence: 99%
“…TWA levels in patients with chronic epilepsy are in the abnormal range, indicating elevated risk for cardiovascular mortality and SCD, and the levels are similar in magnitude to those reported in post‐myocardial infarction patients with significant risk for ventricular tachycardia (Figure 3). 41,50,52–54 Pang et al 41 demonstrated that TWA is present in the severely abnormal range in patients with chronic but not newly diagnosed epilepsy. TWA can be measured on ambulatory EKG monitors, 54 EKG patches, 41 and exercise tolerance testing (ETT) equipment by modified moving average analysis 50,55 …”
Section: A Syndromic Approach To Establishing Clinical Criteria For Epileptic Heartmentioning
confidence: 99%